Phylogeographic evidence for a Florida panhandle–peninsula discontinuity in the distribution of Melitara prodenialis Walker (Lepidoptera: Pyralidae), a native cactus‐boring moth. Issue 4 (12th February 2015) - Marsico, Travis D.; Sauby, Kristen E.; Brooks, Christopher P.; Welch, Mark E.; Ervin, Gary N.; R. Leather, Simon; Ribera, Ignacio
Abstract Insects are highly underrepresented in the phylogeographic literature of the coastal plain region of the southeastern U.S., but they may contribute much to understanding the phylogeographic history of the area. The present study uses Melitara prodenialis Walker, a cactus‐boring moth, to test two alternative hypotheses: Pleistocene changes in environment and coastline associated with population geographic change resulted in (i) a homogeneous Florida, USA, population of M. prodenialis or (ii) isolated subpopulations that gave rise to genetic divergence between regions. Melitara prodenialis larvae were collected from 23 sites (n = 42 larvae sampled). For each larva, a 791 bp sequence of the COI mitochondrial gene was sequenced. Bayesian and parsimony approaches were used to investigate relationships among haplotypes. Phylogeographic and demographic analyses were conducted to identify geographic patterns in haplotype diversity distribution and infer population dynamics over time. Bioclim climate variables from the last interglacial period and the present were used to assess the potential contribution of environmental conditions to phylogeographic patterns observed. Melitara prodenialis populations in the Florida panhandle and peninsula are distinct, and the geographic segregation between these regions is correlated with current and historic climate patterns. Results suggest that populations of M. prodenialis in the Florida peninsula have more recently expanded than those in the panhandle. These findings are consistent with M. prodenialis populations changing in size and distribution following land area and climatic shifts associated with North American cycles of glaciation, with panhandle and peninsula populations remaining segregated over the relevant timeframes.